The Architect's Apprentice - Shafak,Elif; Elif Shafak (London Penguin Random House, 2014)
Summary: Sixteenth century Istanbul: a stowaway arrives in the city bearing an extraordinary gift for the Sultan. The boy is utterly alone in a foreign land, with no worldly possessions to his name except Chota, a rare white elephant destined for the palace menag
Keywords: Historical Fiction -- Istanbul-Turkey -- Turkish Fiction-16th Century